Effect of Nickel Doping on the Optical and Morphological Properties of Titanium Dioxide Nanotubes - Abbasi, S. (Springer Science and Business Media B.V., 2021)
Doping is considered to be one of the effective approaches to modify the properties of TiO2 nanomaterials. The work presented is the investigation on the effect of nickel doping using successive ion layer adsorption-reaction (SILAR) method on the optical and morphological properties of titanium dioxide nanotubes, synthesized by anodizing Ti foil electrochemically. Morphology of the nanotubes is studied under field emission scanning electron microscope (FE-SEM) with EDX result revealed the incorporation of nickel in TiO2 nanotube. The anatase crystal structure of titania was identified by X-ray diffraction (XRD). Furthermore, optical properties of nickel doped TiO2 nanotube are also investigated using UVâVIS spectroscopy, in which red shift is observed, indicating change in the band gap. The promising results of the reduction in the bandgap of the doped TiO2 opens new frontier in the development of sensors and photovoltaic cell, where the bandgap tailoring is essential for an improved performance. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.